Jeanne S. Mintz papers - Mintz, Jeanne S.
Correspondence, professional subject file, speeches and writings, printed material, and other papers documenting Mintz's career as an expert on Indonesia and Southeast Asia. Includes material on her position as analyst and press officer with the Indonesian delegation to the United Nations; her service (1969-1970) with the Dept. of Defense, particularly with COMNAVFORV (Commander Naval Forces Vietnam); and on Indonesian party politics, history, diplomacy, social conditions, and independence from the Netherlands. Also includes an unpublished autobiography of L.N. Palar, head of the United Nations Indonesian delegation from 1948 to 1953.
Correspondents include Arnold C. Brackman, Andrew F. Brimmer, George A. Carroll, Rupert Emerson, Bazri Haznan, Kenneth R. Hill, W.L. Holland, Alice Langley Hsieh, George McTurnan Kahin, Philip E. Lilienthal, Nuradi, L.N. Polnar, Sol S. Sanders, Soedjatmoko (Indonesian ambassador to the U.S.), and Idajat Soejono.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Library of Congress Asian Division.
Asian affairs analyst and official at the U.S. Dept. of Defense. Born 1922, died 1994.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brackman, Arnold C. -- Correspondence; Brimmer, Andrew F. -- Correspondence; Carroll, George A. -- Correspondence; Emerson, Rupert, -- 1899- -- Correspondence; Haznan, Bazri -- Correspondence; Hill, Kenneth R. -- Correspondence; Holland, W. L. -- 1907- -- Correspondence; Hsieh, Alice Langley, -- 1922-1979 -- Correspondence; Kahin, George McTurnan -- Correspondence; Lilienthal, Philip E. -- Correspondence; Nuradi -- Correspondence; Palar, L. N; Palar, L. N. -- Correspondence; Sanders, Sol S. -- Correspondence; Soedjatmoko, -- 1922- -- Correspondence; Soejono, Idajat -- Correspondence; United Nations; United States. -- Department of Defense; United States. -- Naval Forces, Vietnam; Vietnam War, 1961-1975 -- Naval operations, American; Indonesia -- Foreign relations; Indonesia -- History -- 1945-; Indonesia -- History -- Revolution, 1945-1949.; Indonesia -- Politics and government -- 20th century; Indonesia -- Social conditions; Netherlands -- Colonies -- Indonesia; Southeast Asia; Public officials